The Virus and the Glocal: Tracing Semiopolitical Interactions (Glocalism: Journal of Culture, Politics and Innovation, 2020)
This work explores the reactions that the sudden appearance of COVID-19 has caused. More precisely, it is an attempt to grasp the re-articulation of the semiopolitical relations in the first two months of the spread of the virus (or at least of awareness of its circulation). At the heart of this process are the states. We will analyse how some of them managed the unpredictable and the risk represented by the virus. At the same time, we will see how this has brought into play not only the interactions between states, and the interaction between them and the planetary dimension, but also how it has redefined (within each individual state) the form of the collective, that is to say the relationship between rulers and governed, between central government and territories etc. What results is the need for abandoning static definitions of the local and the global in order to trace the multiple glocal relationships that constitute the fabric of our reality.
Keywords: pandemic; semiotics; politics; risk; glocalization